TAMI-16. THREE-DIMENSIONAL ORGANOID CULTURE UNVEILS RESISTANCE TO CLINICAL THERAPIES IN ADULT AND PEDIATRIC GLIOBLASTOMA. (12th November 2021) - Sundar, Swetha; Shakya, Sajina; Wallace, Lisa; Barnett, Austin; Sloan, Andrew; Recinos, Violette; Hubert, Christopher
Abstract: BACKGROUND: Glioblastoma (GBM) is the most common primary brain tumor with a dismal prognosis. The inherent cellular diversity and interactions within tumor microenvironments represent a significant challenge to effective treatment. Traditional culture methods may mask the complexity of such interactions while three-dimensional (3D) organoid culture systems derived from patient cancer stem cells (CSCs) can preserve cellular complexity and microenvironments. Our objective was to determine whether organoid cultures show increased patterns of resistance to potential clinical therapies compared to traditional sphere cultures. METHODS: Adult and pediatric surgical specimens were collected and established as 3D organoids. We created organoid microarrays and visualized bulk and spatially defined differences in cell proliferation using immunohistochemistry (IHC) staining, as well as cell cycle analysis by flow cytometry with 3D regional labeling. We tested the response of CSCs grown in each culture method to temozolomide, ibrutinib, lomustine, ruxolitinib, and radiotherapy using proliferative and viability assays. RESULTS: Compared to sphere cultures from the same patient, organoids showed diverse proliferative cell populations and broad resistance to all therapies tested, albeit with both intraspecimen and interspecimen variability in the extent of resistance. Organoid specimens demonstrated a blunt response to current GBM standard of care therapy (combination temozolomide and radiotherapy) and maintained both cellular proliferation in their outer rim and overall structure and viability compared to the matched sphere specimens. CONCLUSIONS: Our results suggest that growth of tumor specimens as organoid cultures may better reflect the cellular diversity and clinical reality of GBM therapeutic response. Patient-derived GBM organoids offer a valuable complement to traditional culture methods and may have powerful predictive capability of personalized drug sensitivities and therapeutic resistance.